The influence of company size, audit opinion, audit delay, and management changes on auditor switching - Elvira Luthan; Husna Roza; Sri Daryanti Zein; Mella Audya Poetri (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to determine the influence of company size, audit opinion, audit delay, and management change on auditor switching. The population and sample chosen are infrastructure, property and real estate sector companies listed on the Indonesia Stock Exchange for the 2020-2022. The sampling technique used in this research is purposive sampling, and 100 companies meet the criteria as samples. The data analysis method used in the study is logistic regression analysis with a quantitative approach. Research data processing uses the Statistical Product and Service Solutions (SPSS) application software version 25. The results of this study show that management changes have an effect on auditor switching, while company size, audit opinion, and audit delay have no effect on auditor switching.